2023
DOI: 10.3390/ijms24108613
|View full text |Cite
|
Sign up to set email alerts
|

Xenon’s Sedative Effect Is Mediated by Interaction with the Cyclic Nucleotide-Binding Domain (CNBD) of HCN2 Channels Expressed by Thalamocortical Neurons of the Ventrobasal Nucleus in Mice

Nour El Dine Kassab,
Verena Mehlfeld,
Jennifer Kass
et al.

Abstract: Previous studies have shown that xenon reduces hyperpolarization-activated cyclic nucleotide-gated channels type-2 (HCN2) channel-mediated current (Ih) amplitude and shifts the half-maximal activation voltage (V1/2) in thalamocortical circuits of acute brain slices to more hyperpolarized potentials. HCN2 channels are dually gated by the membrane voltage and via cyclic nucleotides binding to the cyclic nucleotide-binding domain (CNBD) on the channel. In this study, we hypothesize that xenon interferes with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…For example neuroimaging evidence fairly unequivocally demonstrates that xenon and nitrous oxide induce changes in subcortical activity, particularly that of thalamus -a major anatomical source for broadband driving. Xenon has been reported to decrease thalamic regional cerebral blood flow [24,25] in clinical studies and to disrupt thalamocortical signal propagation, by inhibiting hyperpolarization-activated type 2 cyclic nucleotide-gated channels, in animal models [26,27]. By contrast nitrous oxide, in the few available studies, is fairly consistently reported to increase thalamic regional cerebral blood flow and glucose metabolism [28,29].…”
Section: Changes In Damping Not Synchrony May Better Explain Changes ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example neuroimaging evidence fairly unequivocally demonstrates that xenon and nitrous oxide induce changes in subcortical activity, particularly that of thalamus -a major anatomical source for broadband driving. Xenon has been reported to decrease thalamic regional cerebral blood flow [24,25] in clinical studies and to disrupt thalamocortical signal propagation, by inhibiting hyperpolarization-activated type 2 cyclic nucleotide-gated channels, in animal models [26,27]. By contrast nitrous oxide, in the few available studies, is fairly consistently reported to increase thalamic regional cerebral blood flow and glucose metabolism [28,29].…”
Section: Changes In Damping Not Synchrony May Better Explain Changes ...mentioning
confidence: 99%
“…However, they each produce a different constellation of effects on the magnetoencephalogram (MEG) and electroencephalogram (EEG). For example, xenon while typically reported to induce increases in low-frequency delta (0 -4 Hz) and theta (4 -8 Hz) band activity, is associated with inconsistent changes in higher frequency alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma activity (> 30 Hz) [1][2][3][4][5][6]. In contrast nitrous oxide is reported to have little or no effect on low frequency delta and theta activity, but is generally identified as suppressing alpha and increasing high frequency gamma [2,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%